ChemInform Abstract: Trifluoroborane‐Catalyzed C—H Functionalization/S—H Insertion Reaction: Construction of N, S‐Acetal Quaternary Centers. Issue 40 (October 2015) - Cai, Yan; Ge, Haihong; Sun, Weize; Miao, Zhiwei
Abstract Mercaptans and thiophenols participate in the insertion reaction with carbenoids generated in situ from α‐diazophosphonates to produce N, S‐acetals containing quaternary centers.